Blood Pressure Variability: Marker or Predictor of Cardiovascular Risk? - A. D. Yuldasheva; G. A. Khamidullaeva (International Journal of Biomedicine, 2023)
Background: Regardless of the mean blood pressure value, short-term and long-term BP variability (BPV) are associated with the development and progression of target organ damage and predictors of cardiovascular complications and mortality. The purpose of the present study was to evaluate the prognostic significance of increased BPV in patients with arterial hypertension (AH). Methods and Results: The study consisted of two stages. In the first stage, a retrospective analysis of 365 ABPM results was carried out. As a result of the analysis, 271 patients aged 56.1±10.0 years with uncontrolled AH Grades 1-3 (ESC/ESH, 2018) were included in this study. Depending on the values of BPV, AH patients were divided into two groups: Group 1 consisted of patients with normal BPV (n=145), and Group 2 consisted of patients with increased BPV (n=126). The second stage included 91 patients with uncontrolled hypertension without permanent antihypertensive therapy who had increased BPV. We found statistically significant differences in BP between the AH patients with normal BPV and increased BPV. Thus, in the group with normal BPV, compared with increased BPV, the parameters of the average 24-h systolic BP (SBP), daytime SBP, and nighttime SBP were statistically lower (141±14.6 vs. 147.2±20.2 mmHg, P<0.004; 142.8±15.1 vs. 148.4±20.7 mmHg, P<0.01; and 136.2±15.5 vs. 143.8±21.4 mmHg, P<0.001; respectively). A statistically significant moderate direct correlation was found between the average 24-h SBP and the average 24-h and daytime SBP variability (SBPV) (rs=0.49 and rs=0.40 respectively, P<0.001 in all cases). A statistically significant moderate to weak direct correlation also was found between the average daytime SBP, and the average 24-h and daytime SBPV (rs=0.45 and rs=0.37, respectively, P<0.001 in all cases). A moderate direct correlation was found between nighttime SBP and 24-hour SBPV (rs=0.52, P<0.001) and between nighttime SBP and daytime SBPV (rs=0.42, P<0.001). Weak direct correlations were found between the average 24-h SBPV and central SBP (SBPc) (rs=0.34, P<0.001), as well as between the average 24-h and daytime SBPV and central pulse pressure (PPc) (rs=0.33 and rs=0.32, respectively, P<0.001 in all cases). A weak direct correlation was found between carotid intima-media thickness (CIMT) and the average 24-h and daytime SBPV (rs=0.37 [P<0.001] and rs=0.3 [P=0.04]). Conclusion: The increased BPV is associated with impaired diurnal blood pressure profile (DBPP) and structural and functional changes in blood vessels, in particular, an increase in SBPc and PP in the aorta, and CIMT thickening, which characterizes increased BPV as a predictor of vascular remodeling in patients with uncontrolled AH.